Про структуру множини неперервних розв’язкiв систем нелiнiйних рiзницевих рiвнянь в околi стану рiвноваги - Акбергенов, А.А.; Пелюх, Г.П. (Нелінійні коливання, 2012)
Построено представление общего непрерывного решения широкого класса систем нелинейных разностных уравнений в окрестности состояния равновесия и исследована его структура. We construct a representation for a general continuous solution to a broad class of nonlinear difference systems in a neighborhood of an equilibrium. We also study the structure of the equilibrium.